COMPETITIVENESS OF THE TOURISM PRODUCT OF KOŁOBRZEG SPA - Andrzej Hadzik; Adam Szromek; Danuta Żylak (Acta Scientiarum Polonorum. Oeconomia, 2010)
Products of the tourism spa are an offer of more and more global health tourism market. In spas desire for competitiveness forces different actions, including product concerning health services and infrastructure. There are numerous factor essential for creating competitiveness of subjects or tourist areas. One of them is innovation applying. Other important factors of spa tourism development are product innovations, including modern health services, i.e. wellness. The aim of the paper is to show the level of competitiveness of some elements of a spa product, especially health services, on the example of Kołobrzeg spa.